Business failure factors in Iranian SMEs: Do successful and unsuccessful entrepreneurs have different viewpoints? - Zahra Arasti; Fahimeh Zandi; Neda Bahmani (Journal of Global Entrepreneurship Research, 2014)
Small and medium Enterprises (SMEs) play a key role to innovation, employment, and competitive advantage. One of the requirements for growth, creativity as well as entrepreneurship in societies is to study their failure process. The purpose of this survey study was to investigate factors which affect business failure from successful versus unsuccessful entrepreneurs' points of view. Our sample includes 120 entrepreneurs in newly established small businesses who work in Iranian industry sector. Data was gathered through questioners around general themes of "immediate environment", "general environment", "manager/entrepreneur", and "corporate policy". Our findings show a significant difference between successful and unsuccessful entrepreneurs' viewpoints and also prioritize the business failure factors.
Keywords: 650; Entrepreneurship; Business failure factors; Successful versus unsuccessful entrepreneurs; Iran